Building Fluorescent DNA Nanodevices on Target Living Cell Surfaces1. Issue 21 (18th April 2013) - Zhu, Guizhi; Zhang, Shengfeng; Song, Erqun; Zheng, Jing; Hu, Rong; Fang, Xiaohong; Tan, Weihong
<x xml:space="preserve">Abstract</x> DNA nanotrain: Anchoring of preformed fluorescent DNA nanodevices (NDs; see picture) and in situ self‐assembly of fluorescent DNA NDs on target living cell surfaces are reported. The in situ self‐assembly of the nanodevice was further shown on surfaces of living cells in cell mixtures. These DNA NDs exhibited fluorescence emission and underwent fluorescence resonance energy transfer (FRET) on living cell surfaces.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>